Liver-Stage Specific Response among Endemic Populations: Diet and Immunity - Dalai, Sarat Kumar; Yadav, Naveen; Patidar, Manoj; Patel, Hardik; Singh, Agam Prasad (Frontiers in Immunology, 2015)
Developing effective anti-malarial vaccine has been a challenge for long. Various factors including complex life cycle of parasite and lack of knowledge of stage specific critical antigens are some of the reasons. Moreover, inadequate understanding of the immune responses vis-à-vis sterile protection induced naturally by Plasmodia infection has further compounded the problem. It has been shown that people living in endemic areas take years to develop protective immunity to blood stage infection. But hardly anyone believes that immunity to liver-stage infection could be developed. Various experimental model studies using attenuated parasite suggest that liver stage immunity might exist among endemic populations. This could be induced because of the attenuation of parasite in liver by various compounds present in the diet of endemic populations.